2007 farm bill: Policy options and consequences for Northeast speciality crop industries, small farms, and sustainability. Report on listening sessions - Nelson Bills; Jerry White (Cornell University, Charles H. Dyson School of Applied Economics and Management, 2006)
This report summarizes Phase I of the project '2007 Farm Bill: Policy Options and Consequences for Northeast Specialty Crop Industries, Small Farms, and Sustainability'. The purpose of Phase I is to solicit information and feedback on specialty crop industry members' views and preferences with respect to the upcoming 2007 Farm Bill. Several aspects of Federal support for specialty crop producers are considered. This information will be used to gauge responsiveness to a wide set of policy options and possible directions for titles that might be incorporated into the next farm bill. These options and directions range from direct income support to enhanced environmental and conservation programming that is tailored to the needs of specialty crop producers. The geographic focus of this report encompasses the Northeastern US, defined here to include 12 states - Connecticut, Delaware, Maine, Maryland, Massachusetts, New Hampshire, New Jersey, New York, Pennsylvania, Rhode Island, Vermont, and West Virginia.
Keywords: 330